Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Tracking a half century of media reporting on gray wolves - Alexander K. Killion; Tracy Melvin; Eric Lindquist; Neil H. Carter (Conservation Biology, 2019)
Natural resource and wildlife managers must balance the disparate priorities of a diversity of stakeholders. To manage these priorities, a firm understanding of topics salient to the public is needed. The media often report on issues of importance to the public; therefore, these reports may be a useful measure of public interest. However, efficient methods for distinguishing diverse topics related to a wildlife management issue reported in the media and changes in the salience of those topics have been lacking. We used latent Dirichlet allocation, a Bayesian mixture model, to quantitatively assess the salience of topics surrounding the gray wolf ( Canis lupus ), which was reintroduced to Idaho (U.S.A.) in 1995. We analyzed articles published from 1960 to 2015 in an Idaho newspaper. We identified 6 distinct topics associated with gray wolves: policy, hunting, biological status, implementation of management, recovery, and human‐wolf conflict. The salience of topics pre‐ and postreintroduction of wolves (1995) and pre‐ and postdelisting of wolves from the U.S. Endangered Species Act (2009) differed significantly, underscoring that these events were turning points in how issues were being publicly discussed and framed. Articles written by the local reporters were more likely to report on topics regarding conflict between humans and wolves, whereas articles sourced from a national outlet reported more on topics pertaining to wolf policy and biological status. In the context of managing a contentious, far‐ranging, and long‐lived wildlife species, our methods can help guide the location and timing of a suite of management strategies (e.g., media relation plans and stakeholder engagement) that promote human‐wildlife coexistence across different landscapes.

Application of Species Distribution Models to Identify Estuarine Hot Spots for Juvenile Nekton - Ann Commagere Hijuelos; Shaye E. Sable; Ann M. O’Connell; James P. Geaghan; David C. Lindquist; Eric D. White (Estuaries and Coasts, 2017)

Recent changes in flood preparedness of private households and businesses in Germany - Heidi Kreibich; Isabel Seifert; Annegret H. Thieken; Eric Lindquist; Klaus Wagner; Bruno Merz (Regional Environmental Change, 2011)